1210Understanding the effect of Helicobacter pylori infection on gastroesophageal reflux disease and Barrett's oesophagus. (2nd September 2021) - Wang, Miss Sabrina; Dashti, Ghazaleh; Hodge, Allison; Kendall, Bradley; Dixon-Suen, Suzanne; Giles, Graham; Milne, Roger; English, Dallas
Abstract: Background: Helicobacter pylori ( H.pylori ) infection causes atrophic gastritis and gastric cancer. Ironically, decreased gastric acid production in those with atrophic gastritis might reduce harmful gastroesophageal refluxate, thereby reducing gastroesophageal reflux disease (GERD) and Barrett's oesophagus (BE) risk. Methods: In two nested case-control studies with 425 GERD and 169 BE cases, we compared sex-specific GERD and BE risk in H.pylori seronegative participants with seropositive participants. Where seronegativity was associated with increased BE risk, we quantified the effect mediated by GERD using a Monte Carlo simulation-based g-computation approach to estimate interventional effects. Moreover, we classified participants into gastritis types using serum pepsinogen-I and gastrin-17 data. Results: For men, H.pylori seronegativity was associated with 1.69-fold (CI:1.03-2.75) and 2.14-fold (CI:1.18-3.88) higher odds for GERD and BE respectively. Five (33%) out of the 15 per 1000 excess BE risk from being seronegative was mediated by GERD. No association was observed for women. Among those seropositive, the proportion with atrophic antral gastritis was higher for men than for women (68% vs 56%; p = 0.015). Conclusions: H.pylori seronegativity was associated with increased GERD and BE risk for men but not women, which could be partly explained by the higher proportion of H.pylori -associated atrophic antral gastritis in men. Evidence of GERD mediating seronegativity's effect on BE supports this explanation. Key messages: Whilst H.pylori infection might reduce GERD and BE risk, this is potentially a by-product of atrophic gastritis, a risk factor for gastric cancer. Treating GERD could partly reduce the excess BE risk for seronegative individuals.